Perbandingan Pengaruh Aktivator Effective Microorganisme 4 (EM 4) dan Promoting Microbes (PROMI) Terhadap Kualitas Kompos Organik Di Industri Galangan Kapal - Rahmadiah Indah Setyoningrum; Syadzadhiya Qothrunada Zakiyayasin Nisa (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Shipbuilding industrial companies still produce a number of organic waste in the form of twigs, grass and leaves. In line with developments in the current era, organic waste that accumulates will become an issue for the environment if it is not managed properly. This activity was carried out to overcome the problem of organic waste in the shipbuilding industry, by utilizing organic waste for composting. Composting is a simple anaerobic method that can be easily carried out in the shipbuilding industry. This method turns organic waste into compost by carrying out a fermentation process. Organic waste in the form of leaves that are turned into compost can increase the nutrient content in the soil. The composting process is carried out using two different activator materials, namely using Effective Microorganisms 4 (EM 4) and Promoting Microbes (PROMI). The results of the compost research carried out have met the quality standards according to SNI 19-7030-2004. The final results of these two treatments are not too different, the pH resulting from the EM4 activator treatment is 6.9 and the pH from the PROMI activator treatment is 7. The temperature value for both does not exceed the ground water temperature, namely the final temperature of the EM4 activator treatment is 29.9oC and from PROMI activator treatment of 30oC. The observation results show that of the two activators EM4 and PROMI, the one that is more effectively used for composting is the EM4 activator because the microorganism content in EM4 has more classifications compared to the PROMI activator.